The effects of peptide IF7-conjugated dendrimer loaded with doxorubicin on colorectal cancer - Omid Reza Tamtaji; Mehdi Shafiee Ardestani; Abdolkarim Talebi Taheri; Michael R. Hamblin; Tina Rahjoo; Fatemeh Nabavizadeh; Hamed Mirzaei (Cancer Nanotechnology)
Abstract We assessed the therapeutic potential of a combination of dendrimer generation 2 (G2) + doxorubicin (DOX) + peptide IF7 on colorectal cells. The researchers utilized regular examinations to assess the dimensions, structure, distribution, and dosage of DOX in the manufactured nanoparticles through physical and chemical evaluations. Afterwards, the MTT (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide) test was used to evaluate how the presence of these nanoparticles affected the ability of HCT116 cells to survive. Finally, both reverse transcription–quantitative polymerase chain reaction (RT–qPCR) and Western blotting methods were used to measure the levels of gene expression in the Wnt/β-catenin signaling pathway, which includes genes, such as β-catenin, cyclin D1, Twist, and Zinc-finger E-box-binding homeobox 1 (ZEB1). In addition, protein expression related to apoptosis (B-cell lymphoma 2 (Bcl2), BCL2 associated X (Bax), and caspase-3) and angiogenesis (vascular endothelial growth factor (VEGF)) was also assessed. The dendrimer G2 + DOX + IF7 had a mean diameter of 165.6 nm, displayed primarily a round form, and had the capability to react to variations in acidity levels. The mixture of dendrimer G2 + DOX + IF7 demonstrated a notable capacity to damage the HCT116 cell line by diminishing the expression of β-catenin, cyclin D1, Twist, and ZEB1 genes. Moreover, it decreased the amounts of VEGF and Bcl2 proteins and increased the levels of Bax and caspase-3 proteins. In conclusion, this combination has an ability to trigger cell death by precisely directing the Wnt/β-catenin and apoptosis pathways.